One more time on the helicity decomposition of spin and orbital optical currents - Aiello, Andrea (Journal of Physics A: Mathematical and Theoretical, 2022)
The helicity representation of the linear momentum density of a light wave is well understood for monochromatic optical fields in both paraxial and non-paraxial regimes of propagation. In this note we generalize such representation to nonmonochromatic optical fields. We find that, differently from the monochromatic case, the linear momentum density, aka the Poynting vector divided by c 2, does not separate into the sum of right-handed and left-handed terms, even when the so-called electric-magnetic democracy in enforced by averaging the electric and magnetic contributions. However, for quasimonochromatic light, such a separation is approximately restored after time-averaging. This paper is dedicated to Sir Michael Berry on the occasion of his 80th birthday.
Created from Fastlane, Scopus look-up
Keywords: helicity; non-monochromatic light; Poynting vector; spin and orbital angular momentum of light